Efektivitas Bambu Air (Equisetum Hyemale) dalam Fitoremediasi untuk Penurunan Kadar COD dan Surfaktan Pada Limbah Laundry - Nara Naomi Aprilia Putri; Raden Kokoh Haryo Putro (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
In general, laundry businesses use detergent rather than soap to wash clothes because detergent contains surfactants that are more effective at removing dirt. This washing process produces waste that is usually disposed of directly into the environment. The indiscriminate disposal of laundry waste can cause environmental pollution because it contains pollutants, such as chemical oxygen demand (COD) and surfactants, that exceed established quality standards. The purpose of this research was to test the effectiveness of water bamboo plants in reducing COD and MBAS levels in laundry waste. This phytoremediation method utilizes microorganisms (rhizosphere microbes) living in the root system and planting media. These microorganisms decompose organic and inorganic materials in wastewater into simpler compounds, which are then used as nutrients by the plants. The most effective configuration for reducing COD and surfactant levels in laundry waste is 15 water bamboo plants with a residence time of three days. However, COD levels are still above the quality standard while surfactant levels are below it.